HUBUNGAN KARAKTERISTIK DAN LAYANAN KESEHATAN DENGAN KEPATUHAN MINUM OBAT ANTIRETROVIRAL (ARV) PADA PENDERITA HIV/AIDS DI RSUD BIAK - Selina Boseren; Inggrit Rita Uli Manik; Peny Wena Betsy Maran (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Until December 2020, there were 206 new cases of HIV/AIDS in Biak Numfor Regency, consisting of 67 HIV cases and 129 AIDS cases, so compliance with ARV taking is very necessary. This type of research uses a research technique with an analytic survey method with a cross sectional approach. In this study, the population was HIV Aids sufferers who visited Biak Hospital to take ARV drugs. The number of samples is 70 people determined by purposive sampling. This data analysis uses the Chi Square test. The results of this study showed that there was no relationship between age characteristics and adherence to taking ARVs with a value of (p) = 0.411, there was a relationship between educational characteristics and adherence to taking ARVs with a value of (p) = 0.005, there was no relationship between duration of treatment characteristics and adherence to taking ARVs with a value of ( p) = 0.168, there is a relationship between gender characteristics and adherence to taking ARVs with a value of (p) = 0.034, there is a relationship between health services and adherence to taking ARVs with a value of (p) = 0.034. Suggestions that health service providers can continue to improve health services so that adherence to ARV treatment increases.